Endometrial mesenchymal stem stromal cells in mature and immature sheep: An in vitro study - Farnaz Ghobadi; Farhad Rahmanifar; Davood Mehrabani; Amin Tamadon; Mehdi Dianatpour; Shahrokh Zare; Iman Razeghian Jahromi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Endometrial mesenchymal stem stromal cells (EnMSCs) are critical for uterine function, repair, and regeneration. Objective: This study introduced isolation technique of EnMSCs and compared the characteristics of EnMSCs in mature and immature ewes. Materials and Methods: Endometrial tissue samples from the uterus of 10 ewes were collected from the slaughterhouse. Endometrial cells were isolated from tissue using cold incubation and then chopping and treating was performed with collagenase type I. Isolated cells were cultured in cell culture medium and then attached cells to flasks were harvested as EnMSCs and subcultured. To enumerate the cells, the population doubling time (PDT) was determined and 2.2×104 cells in passage 4 were seeded into 24-well culture plates to compare the growth curves of isolated cells. Reverse transcription polymerase chain reaction (RT-PCR) was performed for detection of CD34 and CD73 markers. The osteogenic and adipogenic potential of isolated cells were determined using differentiation tests. Results: EnMSCs adhered to the flasks and displayed spindle-shape. Based on findings of the cell count and the growth curves, the EnMSCs growth was significantly more prominent in immature ewes in comparison to mature sheep. The PDT of EnMSCs in immature ewes was about 21 hr whereas this time period was two times higher (45 hr) in mature sheep. RT-PCR analyses of EnMSCs were positive for CD73 and negative for CD34. EnMSCs were differentiated into osteoblasts and adipocytes. Conclusion: Based on mesenchymal stem cells characters confirmed in EnMSCs, they can be a candidate for cell therapy and regenerative medicine.